Brain‐based treatment—A new approach or a well‐forgotten old one?. Issue 4 (24th April 2018) - Matanova, Vanya; Kostova, Zlatomira; Kolev, Martin
Abstract: For a relatively long period of time, mental functioning was mainly associated with personal profile while brain functioning went by the wayside. After the 90s of the 20th century, or the so called "Decade of the Brain", today, contemporary specialists work on the boundary between fundamental science and medicine. This brings neuroscience, neuropsychology, psychiatry, and psychotherapy closer to each other. Today, we definitely know that brain structures are being built and altered thanks to experience. Psychotherapy can be more effective when based on a neuropsychological approach—this implies identification of the neural foundations of various disorders and will lead to specific psychotherapeutic conclusions. The knowledge about the brain is continually enriched, which leads to periodic rethinking and updating of the therapeutic approaches to various diseases of the nervous system and brain dysfunctions. The aim of translational studies is to match and combine scientific areas, resources, experience and techniques to improve prevention, diagnosis and therapies, and "transformation" of scientific discoveries into potential treatments of various diseases done in laboratory conditions. Neuropsychological studies prove that cognition is a key element that links together brain functioning and behaviour. According to Dr. Kandel, all experimental events, including psychotherapeutic interventions, affect the structure and function of neuronal synapses. The story of why psychotherapy works is a story of understanding the brain mechanisms of psychic processes, a story of how the brain has been evolving to ensure learning, forgetting, and the mechanisms of permanent psychological change. The new evidence on brain functioning necessitates the integration of neuropsychological achievements in the psychotherapeutic process. An integrative approach is needed to take into account the dynamic interaction between brain functioning, psyche, soul, spirit, and social interaction, ie, development of a model of psychotherapeutic work based on cerebral plasticity! Brain‐based psychotherapy aims at changing brain functioning not directly, but through experiences. This is neuro‐psychologically informed psychotherapy.